The Primacy of Accessibility in Urban Riverfront Tourism: An Empirical Integration of the 3A-TPB Framework in Banjarmasin, Indonesia - Arafat Alhally; Sahara Maghfiroh; Padli (Journal of Tourism Sustainability, 2026)
Urban riverfronts represent strategic recreational assets where terrestrial and aquatic mobility systems converge. Despite their economic significance, the psychological mechanisms governing visit decisions in high-density land-water interfaces remain insufficiently understood. This study examines the impact of attractions, amenities, and accessibility on visitor decisions at Siring Piere Tendean, Banjarmasin, using an integrated 3A-Theory of Planned Behavior (TPB) framework. Utilizing a quantitative survey (n=100) analyzed via multiple linear regression, the findings demonstrate that 3A attributes account for 52.6% of the variance in visit decisions. Notably, accessibility emerges as the dominant predictor, surpassing the influence of amenities and attractions. The data reveal that for the 83% of respondents who are repeat visitors, the riverfront operates as a functional utility hub where behavioral execution is dictated by the absence of mobility friction. Theoretically, this research anchors Perceived Behavioral Control in physical accessibility, establishing a "mobility-control link" in dense urban settings. Practically, the results advocate for a transition toward mobility-centric governance that prioritizes the synchronization of docking facilities and pedestrian connectivity to sustain destination competitiveness.